PERANG SALIB SERTA DAMPAKNYA BAGI DUNIA ISLAM DAN EROPA - Aniroh Aniroh (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
Crusades were a series of waves of armed religious strife started by Christians in the period 1095-1291, with the aim of reclaiming Jerusalem and the "Holy Land" from Muslim rule. The Crusades had a significant impact on Europe, which was adapted to a more advanced Islamic civilization from various sides.  The crusade occurred due to several factors including religious factors, political factors and economic factors.For Europe, the Crusades contributed a lot to the development of European civilization and culture. The progress of Western science and civilization today cannot be separated from the contacts between the West and the East that lasted for centuries during the Crusades.Keywords: Crusades, Islam, Europe